Analysis of Electromagnetic Properties of Doubly-fed Turbine Generator - Ding Shuye; Zhang Ning (Institute of Advanced Engineering and Science, 2013)
For the sake of studying the electromagnetic properties of doubly-fed turbine generator. This paper proposed a method which adds an equivalent impedance to simulate the doubly-fed turbine generator’s rated state in Maxwell Circuit Editor. Time–stepping finite element was adopted to calculate. Transfer radial air-gap flux density as FFT, getting harmonic content and the influence of harmonic wave on loss. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2006